2007
DOI: 10.2174/092986707780059698
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Peptides for the Immunodiagnosis of Human Diseases

Abstract: Synthetic peptides have been shown to be valuable tools for viral laboratory diagnosis and can provide uniform, chemically well-defined antigens for antibody analysis, reducing inter- and intra-assay variation. The main aim in the development of peptide-based diagnostic tests is to recognise specific antibodies induced by the whole viral proteins but using selected short fragments containing the most potent antigenic determinants. The success of this approach depends on the extent to which synthetic peptides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 87 publications
1
71
0
2
Order By: Relevance
“…1. Inexpensive and rapid point-of-care (POC) tests based on the detection of antibodies to antigens and/or epitopes selected by a careful analysis of their immunogenic potential in patients and controls have been devised for other diseases (1,13). However, a recent WHO-sponsored analysis of the performances of currently available commercial serological tests for TB diagnosis showed that none of these tests provide accurate and reliable results for either pulmonary or extrapulmonary TB patients (46,47,56).…”
Section: Discussionmentioning
confidence: 99%
“…1. Inexpensive and rapid point-of-care (POC) tests based on the detection of antibodies to antigens and/or epitopes selected by a careful analysis of their immunogenic potential in patients and controls have been devised for other diseases (1,13). However, a recent WHO-sponsored analysis of the performances of currently available commercial serological tests for TB diagnosis showed that none of these tests provide accurate and reliable results for either pulmonary or extrapulmonary TB patients (46,47,56).…”
Section: Discussionmentioning
confidence: 99%
“…According to World Health Organization estimates, ϳ9 ϫ 10 6 new cases of tuberculosis (TB) and ϳ2 ϫ 10 6 TB-related deaths occur every year. The major proportion (Ͼ90%) of these cases and deaths occur in low-income developing countries where the diagnosis of TB is based primarily on the examination of sputum smears for acid-fast bacilli.…”
mentioning
confidence: 99%
“…In recent years, antigen discovery has been accelerated by the development of high-throughput screening assays such as microarray screening that allows the rapid selection of target potential candidate antigens from large numbers of proteins (22,25 Several immunodiagnostic tests based on synthetic peptides derived from carefully selected highly antigenic proteins have been devised for viral, bacterial, and parasitic diseases in recent years (3,6,17). In the current studies, we have screened libraries of overlapping peptides of immunogenic proteins identified from our microarray studies to investigate the feasibility of using selected peptides rather than recombinant proteins to devise a diagnostic test for TB.…”
mentioning
confidence: 99%
“…28 Compared with native antigens, synthetic peptides and recombinant proteins are considered superior for immunodiagnostic purposes, because they are well-defined and can be produced in large quantities. 29,30 However, the low diagnostic sensitivities and specificities of some recombinant proteins remain a significant challenge in the serodiagnosis of CE. 31 For example, 34 CE samples, which were positive with native Ag5, showed diagnostic sensitivities of 65% and 21% when tested with rAg5 and a 38-kDa subunit of rAg5, respectively.…”
Section: Discussionmentioning
confidence: 99%